Bodies - Tuxworth, Nicola (New York : Lorenz Books, 1996)
Color pictures and simple text provide very young readers with information about the different parts of their bodies.
2.2
K-3
K-3
Keywords: Human body -- Juvenile literature; Human body; Human body